Serum nerve growth factor beta, brain‐ and glial‐derived neurotrophic factor levels and psychopathology in unmedicated patients with schizophrenia. Issue 6 (June 2018) - Chu, Che‐Sheng; Chu, Chin‐Liang; Wu, Chih‐Ching; Lu, Ti
Abstract : Background: : There is accumulating evidence that neurotrophic factors may be involved in the pathophysiology of patients with schizophrenia. This study aimed to explore the relationship between serum nerve growth factor beta (NGF‐beta), brain‐derived neurotrophic factor (BDNF), and glial‐derived neurotrophic factor (GDNF) levels and psychopathology in unmedicated patients with schizophrenia. Methods: : Serum NGF‐beta, BDNF, and GDNF levels were determined using enzyme‐linked‐immunosorbent assay (ELISA) in the serum of 30 unmedicated patients with schizophrenia. Symptomatology was assessed with the expanded version of the 24‐items brief psychiatric rating scale (BPRS‐E), which was divided into four conceptual domains: manic excitement/disorganization, depression/anxiety, negative symptoms, and positive symptoms. Kolmogorov–Smirnov one sample test was performed to test non‐parametric variables. Spearman's correlation was performed to examine the correlations between the cytokines of interest and psychopathology. Benjamini‐Hochberg procedure was applied for multiple corrections. Results: : Serum GDNF levels correlated negatively with the BPRS‐total (r = −0.533, corrected p = 0.002) and BPRS‐manic (r = −0.456, corrected p = 0.011) subtests. BDNF levels showed a positive correlation with BPRS‐total (r = 0.480, corrected p = 0.007). In addition, NGF‐beta did not associate with psychopathology measured by BPRS scores. Conclusion: : Neurotrophic factors play a vital role in the regulation of neuroplasticity and neurogenesis in humans. This study suggests that BDNF and GDNF may be contributing to the pathological mechanisms involved in unmedicated patients with schizophrenia.